Stakeholders perspectives on time horizon and quantification of enterprise architectures benefits/value drivers - Rodrigues, Luis Silva (2018)
Enterprise Architectures are being used by many organizations as a strategic tool for framing and managing key business and IT initiatives and activities. However, given the complexity and costs associated with building an Enterprise Architecture, there is a growing need to demonstrate the importance and usefulness in terms of the value that it represents to an organization. Without an adequate justification for the investment in Enterprise Architecture projects, organizations either do not to start or tend to abandon their Enterprise Architectures. In this paper, we present the stakeholders perspectives on two key dimensions of the Enterprise Architectures benefits/value drivers: the time horizon (time needed for the realization of the benefits) and its quantification (measurement of the realization of the benefits). In our view, these two dimensions are fundamental to realize how much effort will be required to assess the value of an Enterprise Architecture.